Global evangelicalism : theology, history and culture in regional perspective - Lewis, Donald M.; Pierard, Richard V., 1934- (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2014)
"Over the past century, evangelicalism has taken on global proportions, spreading from its northern heartlands and forming new and burgeoning centers of vibrant life in the global South. Now, in Global Evangelicalism, a gathering of front-rank historians offer conceptual and regional overviews of evangelical Christianity." --Back Cover
Part I. Theoretical issues. Defining evangelicalism / Mark A. Noll -- The theological impulse of evangelical expansion / Wilbert R. Shenk -- Globalization, religion and evangelicalism / Donald M. Lewis -- Part II. Evangelicalism at ground level regional case studies. Europe and North America / John Wolffe and Richard V. Pierard -- Africa / Ogbu Kalu -- Latin America / t
Includes indexes.
Includes bibliographical references and index.
Keywords: Evangelicalism